Keefektifan Perlakuan Fisik dan Minyak Atsiri untuk Mengeliminasi Bakteri Clavibacter michiganensis subsp. michiganensis pada Benih Tomat - Siti Tri Wahyuni; Ali Nurmansyah; Giyanto Giyanto (Jurnal Fitopatologi Indonesia, 2017)
Clavibacter michiganensis subsp. michiganensis is the causal agent of bacterial canker disease of tomato. The bacteria is seed borne and may cause yield loss up to 70%. Seed treatment is an alternative method for controlling bacterial canker. The objective of the research was to study the effectiveness of physical and essential oil treatment for elimination of C. michiganensis subsp. michiganensis from tomato seed. Research was conducted in 4 separate experiments, i.e. (1) screening essential oils to control C. michiganensis subsp. Michiganensis; (2) to determine the treatment window of physical and essential oil treatment; (3) to determine the physical and essential oil treatment on tomato seed infested by C. michiganensis subsp. Michiganensis; and (4) to determine the effectiveness of treatment combination of physical and essential oil. The results showed that betel oil at concentration of 8% had the greatest inhibitory level (approximately 27.33 mm). Hot water treatment (53 °C) for 25 minutes reduced 90.94% of C. michiganensis subsp. michiganensis population; whereas dry heat treatment (60 °C, 24 hours) and betel oil treatment at 0.25% concentration reduced C. michiganensis subsp. michiganensis population (85.13 and 99.82% respectively). The combination of betel oil (0.5%), hot water (55 °C), and dry heat treatments (60 °C) was the most effective control method, because it reduced 99.99% of C. michiganensis subsp. michiganensis population and maintained the germination level of seed up to 100%.  This combination might be recommended for seed treatment to eliminate C. michiganensis subsp. michiganensis.